RETRACTED: Majid et al. An Extensive Pharmacological Evaluation of New Anti-Cancer Triterpenoid (Nummularic Acid) from Ipomoea batatas through In Vitro, In Silico, and In Vivo Studies. Molecules 2022, 27, 2474 - Muhammad Majid; Anam Farhan; Muhammad Imran Asad; Muhammad Rashid Khan; Syed Shams ul Hassan; Ihsan-ul Haq; Simona Bungau (Molecules)
The journal retracts the article “An Extensive Pharmacological Evaluation of New Anti-Cancer Triterpenoid (Nummularic Acid) from Ipomoea batatas through In Vitro, In Silico, and In Vivo Studies” [...]